Development and validation of a patient-reported questionnaire assessing systemic therapy induced diarrhea in oncology patients - Michelle Lui; Daniela Gallo-Hershberg; Carlo DeAngelis (Health and Quality of Life Outcomes, 2017)
Abstract Background Systemic therapy-induced diarrhea (STID) is a common side effect experienced by more than half of cancer patients. Despite STID-associated complications and poorer quality of life (QoL), no validated assessment tools exist to accurately assess STID occurrence and severity to guide clinical management. Therefore, we developed and validated a patient-reported questionnaire (STIDAT). Methods The STIDAT was developed using the FDA iterative process for patient-reported outcomes. A literature search uncovered potential items and questions for questionnaire construction used by oncology clinicians to develop questions for the preliminary instrument. The instrument was evaluated on its face validity and content validity by patient interviews. Repetitive, similar and different themes uncovered from patient interviews were implemented to revise the instrument to the version used for validation. Patients starting high-risk STID treatments were monitored using the STIDAT, bowel diaries and EORTC QLQ-C30. The STIDAT was evaluated for construct validity using exploratory factor analysis (EFA) using minimal residual method with Promax rotation, reliability and consistency. A weighted scoring system was developed and a receiver-operating characteristic (ROC) curve evaluated the tool’s ability to detect STID occurrence. Median scores and variability were analysed to determine how well it differentiates between diarrhea severities. A post-hoc analysis determined how diarrhea severity impacted QoL of cancer patients. Results Patients defined diarrhea based on presence of watery stool. The STIDAT assessed patient’s perception of having diarrhea, daily number of bowel movements, daily number of diarrhea episodes, antidiarrheal medication use, the presence of urgency, abdominal pain, abdominal spasms or fecal incontinence, patient’s perception of diarrhea severity, and QoL. These dimensions were sorted into four clusters using EFA – patient’s perception of diarrhea, frequency of diarrhea, fecal incontinence and abdominal symptoms. Cronbach’s alpha was 0.78; kappa ranged from 0.934–0.952, except for abdominal spasms (κ = 0.0455). The positive predictive value was 96.4%, with the minimum score of 1.35 predicting a positive STID occurrence. Patients with moderate or severe diarrhea experience significant decreases in QoL compared to those with no diarrhea. Conclusions This is the first patient-reported questionnaire that accurately predicts the occurrence and severity of diarrhea in oncology patients via assessing several bowel habit dimensions.